2022
DOI: 10.1101/2022.08.23.505008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mood variability during adolescent development and its relation to sleep and brain development

Abstract: Background: Mood swings, or mood variability, are associated with negative mental health outcomes. Since adolescence is a time when mood disorder onset peaks, mood variability during this time is of significant interest. Understanding biological factors that might affect mood variability, such as sleep and structural brain development, could elucidate the mechanisms underlying mood disorders. Methods: Data from the longitudinal Leiden Self-Concept study (N=171) over 5 timepoints was used to study the associat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…Conversely, about 40% of Hispanic adolescents reported feelings of worry, anger, loneliness, or frequent crying during the pandemic. While most negative mood changes among adolescents are not necessarily indicative of severe mental health issues, some reported symptoms may be suggestive of depression or anxiety [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, about 40% of Hispanic adolescents reported feelings of worry, anger, loneliness, or frequent crying during the pandemic. While most negative mood changes among adolescents are not necessarily indicative of severe mental health issues, some reported symptoms may be suggestive of depression or anxiety [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Several age-comparative studies using EMA or e-diary methods (Box 1) find more frequent mood changes, operationalized as mood variability and mood instability (Glossary), particularly in mid-adolescence as compared to early [39,40], or late adolescence [40,41]. Of note, there is evidence for more pronounced mood variability in girls than in boys [39][40][41][42].…”
Section: Real-life Assessment Of Daily Mood Fluctuations In Developmentmentioning
confidence: 99%
“…Mood variability, which is defined as the day‐to‐day fluctuation in positive and negative mood states, is an important psychological state that differs between individuals and changes with developmental stages. Understanding mood variability is important as specifically negative mood variability is often associated with increased feelings of anxiety and depression and precedes future symptoms of anxiety and depression (Maciejewski et al, 2014 ; Toenders et al, 2022 ). Prior research showed that negative mood variability shows a peak in adolescence, possibly reflecting a period in which more day‐to‐day fluctuation in negative mood is more prevalent (Maciejewski et al, 2015 ; Toenders et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding mood variability is important as specifically negative mood variability is often associated with increased feelings of anxiety and depression and precedes future symptoms of anxiety and depression (Maciejewski et al, 2014 ; Toenders et al, 2022 ). Prior research showed that negative mood variability shows a peak in adolescence, possibly reflecting a period in which more day‐to‐day fluctuation in negative mood is more prevalent (Maciejewski et al, 2015 ; Toenders et al, 2022 ). This peak is specifically strong in females in mid‐adolescence (Toenders et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation